Hiperrealitas Social Media dan Perilaku Konsumtif Mahasiswa Urban Kampus Pendidikan - Febriana, Putri (Paradigma, 2025)
Abstract Technological advances support the emergence of new social media which is increasingly mushrooming. One of the results of the development of social media is the emergence of TikTok which has gained popularity, especially among student audiences. Tiktok has various kinds of content which sometimes includes promotional actions. Content that is packaged in such a way in various persuasive ways can lead to consumer consumer behavior. Moreover, TikTok is not just a social media, but also provides an online shopping platform directly through the TikTok application. The aim of this research is to identify the mechanism for the consumptive behavior of urban students using the TikTok application as well as the hyper-reality of promotions in TikTok content. This type of research is qualitative research that uses data collection techniques in the form of observation, interviews and documentation. The use of theory in this research carries Jean Baudrillard’s theory of hyperreality. The research subjects were urban students who used the TikTok platform and had shopped online from product advertisements in TikTok content. The results of this research show that most urban students are attracted to advertisements in TikTok content because of the unique and creative packaging, although it often contains hyper-reality. The products that are most in demand are fashion or beauty products. Kemajuan teknologi mendukung kemunculan media sosial baru yang semakin menjamur. Salah satu hasil perkembangan media sosial adalah kemunculan tiktok yang mendapatkan popularitas khususnya pada khalayak mahasiswa. Tiktok memiliki berbagai macam konten yang terkadang terdapat tindakan promosi di dalamnya. Konten yang dikemas sedemikian rupa dengan berbagai cara persuasif dapat menggiring ke arah perilaku konsumtif penggunanya. Terlebih tiktok bukan sekedar media sosial, melainkan juga menyediakan platfrom berbelanja online langsung mealui aplikasi tiktok. Tujuan dari penelitian ini untuk mengidentifikasi mekanisme terjadinya perilaku konsumtif mahasiswa urban pengguna aplikasi tiktok serta hiperealitas promosi dalam konten tiktok. Jenis penelitian ini merupakan penelitian kualitatif yang menggunakan teknik pengumpulan data berupa observasi, wawancara, serta dokumentasi. Penggunaan teori dalam penelitian ini mengusung teori hiperrealitas Jean Baudrillard. Subjek penelitian merupakan para mahasiswa urban pengguna platfrom tiktok dan pernah melakukan belanja secara online dari iklan produk dalam konten tiktok. Adapun hasil dari penelitian ini mendapatkan fakta bahwa kebanyakan mahasiswa urban tertarik dengan iklan dalam konten tiktok karena pengemasan yang unik dan kreatif meskipun terdapat hiperrealitas di dalamnya. Produk yang paling banyak diminati adalah produk fashion dan produk kecantikan atau kosmetik. Keywords: Hyperreality, Consumptive Behavior, Tiktok